Numerical and experimental investigation of mixing enhancement in the passive planar mixer with bent baffles - Yuan, Shuai; Jiang, Bingyan; Jiang, Fengze; Drummer, Dietmar; Zhou, Mingyong (International Journal of Heat and Mass Transfer, 2022)
As an important pre-treatment part of the micro-total analysis system, the micromixer that ensures the uniform mixing of samples and reagents in a short distance is essential for the improvement of the detection accuracy. Here, a type of passive planar micromixer with narrow gaps and obstacles arranged in the mixing units is proposed. The mixer utilizes the micro-jets and bent baffles to split and recombine streams and promote vortex formation, which breaks the laminar flow when the Reynolds number ( Re ) varies from 0.1 to 50. The performance of the unoptimized mixer decreases first and then increases with the increase of Re . However, a poor mixing quality is found in the range of 0.5 < Re < 15. To surmount the above shortcomings, a comprehensive geometrical study is performed on this micromixer and the effects of various parameters such as the width and length of the gap, the shape of the baffle, and mixing unit on the mixing quality and pressure drop are analyzed. The results show that the reduction of gap width and the increase of the gap length result in the improvement of mixing efficiency. The staggered Z-shaped baffles accelerate the mixing process compared to traditional V-shaped baffles owing to asymmetric flow and vortex, which leads to excellent mixing. The results also show that the octagonal mixing unit increases mixing efficiency without basically changing pressure drop because the progressive and tapered structure enhances the convection. Lastly, a novel micromixer whose mixing performance is close to 0.8 at Re = 0.5 at the short distance of 2800 mu m is proposed, fabricated and tested. This work provides a reference for the development of high-efficiency mixers in the pre-processing part of the micro-total analysis system.(c) 2022 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2022-05-27
Keywords: Micromixer; Micro-jet; Z-shaped baffle; Mixing efficiency